2002
DOI: 10.1080/01650250143000265
|View full text |Cite
|
Sign up to set email alerts
|

Quality of child care in the preschool years: A comparison of the influence of home care and day care characteristics on child outcome

Abstract: One hundred and six families of 2-year-old children, having experienced either family day care or centre-based day care, took part in this study. Parents’ and day care providers’ representations and values concerning their ideal definition of child care were assessed, and direct observations of child care settings conducted, using a time-sampling procedure. The instruments concerning both representations and observations have a seven dimension structure: caregiver availability, stimulation, firmness, warmth, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 39 publications
2
13
0
3
Order By: Relevance
“…However, similar to recent findings (e.g., Pierrehumbert et al, 2002;Sylva et al, 2008), we found the effects of preschool quality were as strong as those of the home environment quality.…”
Section: Discussionsupporting
confidence: 79%
“…However, similar to recent findings (e.g., Pierrehumbert et al, 2002;Sylva et al, 2008), we found the effects of preschool quality were as strong as those of the home environment quality.…”
Section: Discussionsupporting
confidence: 79%
“…A more detailed analysis at the ITERS-R item level allowed for the recognition that, besides items related to interactions and language, some items related to personal care routines (i.e., diapering/ toileting, safety practices, health practices) are also among the items most valued by parents and teachers. Several studies developed in Portugal and other countries (e.g., Folque 1995;Cryer and Burchinal 1997;Pierrehumbert et al 2002), following the same or different methodologies, have obtained similar results: interactions between teachers and children as well as healthrelated practices are highly valued by parents. Although all the ITERS-R items were considered important, sand and water play and promoting acceptance of diversity were among the items with lower mean scores for both parents and teachers.…”
Section: Discussionsupporting
confidence: 54%
“…The comparison between teachers and mothers established the following: (a) teachers tended to consider themselves more important for child development than mothers did; (b) teachers tended to show less directive and less academically oriented attitudes towards the education of children than mothers, placing more emphasis on social development; (c) teachers tended to place a higher value on tasks promoting children's development, while mothers placed a higher value on tasks related to social rules, health, and safety (ECCE Study Group 1997). In a study developed in Switzerland by Pierrehumbert et al (2002), parents' and daycare providers' perceptions were compared. The authors emphasized that childcare providers seemed to place a higher value on the "professional" aspects of care, such as the availability (i.e., being patient, available, competent, attentive) and organization (i.e., a safe and healthy environment and caregiver sensitiveness to child's physical well-being), while mothers placed a higher value on relational aspects of care, such as warmth (i.e., caregiver responsiveness and joyful, positive interactions).…”
Section: Parents' and Teachers' Perceptions Of Ece Quality Criteriamentioning
confidence: 99%
“…Among the very few studies which analyze differences between parents and ECEC professionals, most look at differences in ideas and perceptions about ECEC quality (e.g. ECCE Study Group 1997; Pierrehumbert et al 2002;Weaven and Grace 2010;Harris and Tinning 2012). To our knowledge, there is only one study which focuses on reported quality levels and also considers the ECEC professionals' assessments.…”
Section: Previous Studies and Differences In Information Asymmetriesmentioning
confidence: 99%